Implementasi Model Pembelajaran Proyek Warga Global dalam Pembelajaran Pendidikan Kewarganegaraan - Sutrisno, Sutrisno; Sapriya, Sapriya; Komalasari, Kokom; Rahmad, Rahmad (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the planning, implementation, assessment, and characteristics of the global citizen project learning model in civic education learning. This study used qualitative research with a qualitative descriptive approach. Data collection techniques and data sources were obtained from interviews, observations, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and verification. The results and discussion in this article indicated that the planning of a global citizen project learning model was carried out by preparing a learning planning design that includes approaches, methods, models, media, and learning evaluations. The implementation of the global citizen project learning model was carried out with the concept of blended learning in two meetings based on the syntax of the global citizen project learning model consisting of topic determination, project design, implementation, evaluation, and publication. The assessment of the learning model of the global citizen project was carried out using observation sheets, written and oral test formats, as well as the observation sheet format for evaluating the results of global citizen project products. There are six characteristics of the global citizen project learning model in civic education learning, i.e. developing religious attitudes of faith, piety, and character; tolerance; global insight; critical, creative, and innovative thinking; collaboration and communication, and media literacy.